186 Platelets as Key Regulators of Fibrin-Clot Architecture as Assessed by Fractal Analysis of Viscoelastic Properties; Effects of Standard Anti-Platelet Therapies. (3rd June 2016) - Knowles, Rebecca; D'Silva, Lindsay; Armstrong, Paul; Chan, Melissa; Lawrence, Matthew; Standford, Sophie; Sabre, Ahmed; Tucker, Arthur; Williams, Phylip; Warner, Timothy; Evans, Phillip
Abstract : Introduction: Platelets are critical drivers of thrombus formation with high on-treatment platelet reactivity despite dual antiplatelet therapy (DAPT) representing a risk factor for thrombosis. Coagulation pathways also play a central role and configuration of the fibrin network is a vital determinant of clot stability and outcome, with dense clots composed of compact thin fibres associated with thrombotic events. However, despite the interwoven nature of platelet activation and the coagulation system, studies relating both aspects of thrombosis in the same population are limited. Methods: Four groups of healthy volunteers (n = 8) received single anti-platelet therapy aspirin (75 mg) or prasugrel (10 mg) or DAPT with aspirin (75 mg) plus prasugrel (10 mg) or aspirin (75mg) plus ticagrelor (90mg) for 7 days. In this study, we characterised the influences of these standard anti-platelet therapies on platelet function using standard tests of platelet activation and aggregation. We then associated platelet reactivity to fibrin clot microstructure which was determined using advanced rheological techniques to analyse the viscoelastic properties of incipient clots; fractal dimension (D f ) and mean relative mass (RM). Results: Aspirin alone caused inhibition of platelet responses to arachidonic acid (AA), but did not reduce ATP release, P-selectin or PAC-1 binding. Aspirin also had no effect upon the measures of clot structure D f (1.71 ± 0.01 to 1.69 ± 0.01, p = 0.41) or RM (-8 ± 19%, p = 0.47). Prasugrel significantly reduced D f (1.72 ± 0.02 to 1.67 ± 0.01, p = 0.03) and RM(-40 ± 11%, p = 0.03), as well as caused a significant decrease in ATP release, PAC-1 and p-selectin expression (p < 0.05). Both aspirin plus prasugrel and aspirin plus ticagrelor inhibited platelet responses to all agonists tested and decreased P-selectin expression. Significant platelet inhibition was associated with a reduction in D f ; 1.73 ± 0.02 to 1.68 ± 0.02 (p = 0.03) and 1.72 ± 0.03 to 1.62 ± 0.02 (p = 0.04) by aspirin+prasugel and aspirin+ticagrelor, respectively. This corresponded to reductions in RM both for aspirin plus prasugrel (-35 ± 16% change, p = 0.04) and for aspirin plus ticagrelor (-45 ± 14% change, p = 0.04). Conclusion: We demonstrate that platelets are important determinants of clot microstructure which is modifiable by anti-platelet therapies. These therapies may rely on their abilities to reduce thrombus density to exert their therapeutic effects with increased levels of platelet inhibition associated with the formation of more open, porous fibrin clots. We also suggest that it is activation of P2Y12 receptors rather than TX (A2 ) receptors that are key to clot formation. We conclude that there lies both diagnostic and therapeutic potential in determining the functional relationship between platelet reactivity, eventual clot quality and clinical outcome and D f could be a useful novel biomarker in risk stratification and tailored anti-platelet therapies.